Impact of fortifying wheat flour with folic acid on neural tube defects in Lima, Peru - Sanabria Rojas, Hernán (2013)
Observational epidemiologic studies conducted during the past years in several countries reported favorable associationbetween wheat flour fortified with folic acid and reduced cases of neural tube defects (NTD). Objectives: To determine the globalincidence rate (GIR) of neuronal tube defects (NTD) and their reduction in the post-fortifying phase (2006-2010) of wheat flour withfolic acid. Design: Observational, descriptive and retrospective study. Setting: Instituto Nacional Materno Perinatal - INMP, Peru.Participants: Neonates. Interventions: We reviewed 88 236 medical histories of neonates born between 2006 and 2010 and average,standard deviations, absolute and relative frequencies were obtained. NTD trend was measured statistically by Prais Winsten. Poissontest was used to measure 95% CI for GIR of NTD. Main outcome measures: Global incidence rate (GIR) of NTD. Results: A total of 77medical histories were found to have NTD, representing a GIR of 8.7 per 10 000 (95% CI: 6,9-10,9) neonates. The highest incidenceof 15.6 per 10 000 (95% CI: 10.2-22.9) was found in 2006 and the lowest 7.61 per 10 000 (95% IC: 4,1-13,0) in 2010. Incidences byNTD types were: spina bifida 6.7 per 10 000 (95% CI: 5.1-8.6), anencephaly 1.9 per 10 000 (95% CI: 1.1-3.1), and encephalocele 1per 10 000 (95% CI: 0.1-0.6). Conclusions: NTD incidence at INMP decreased to 8,7 x 10 000 neonates during 2006-2010 after use ofwheat flour fortified with folic acid, which provides positive evidence of the intervention impact.